Fostering Unity in Diversity: Ki Hadjar Dewantara’s Vision for Multicultural Education - Windria, Hening; Maksum, Arifin; Nurhasanah, Nina (Journal of Education Research, 2024)
Significant in building unity. To overcome this complex problem requires an education system that prioritizes unity with tolerance and respects cultural differences. This article explores Ki Hadjar Dewantara’s vision in multicultural education as an effort to realize the motto "Bhinneka Tunggal Ika" in the context of Indonesian education. Ki Hadjar Dewantara, as a pioneer of national education, emphasized the importance of inclusive education, rooted in local cultural values, and respecting diversity. This article analyzes his ideas through a historical and conceptual approach, highlighting educational principles such as Tri-N (Niteni, Nirokke, and Nambahi) and an understanding of the socio-cultural environment of students. The results of the study show that multicultural education based on Ki Hadjar Dewantara’s thoughts is relevant to building awareness of diversity, instilling values ​​of tolerance, and strengthening national character in the younger generation. In the era of globalization, this vision is a strategic foundation for strengthening unity amidst differences, creating a harmonious society, and preparing students to face global challenges without losing their identity as the Indonesian nation